Near sunlight continuous broadband white-light emission by single-phase Zn(ii)-1, 3, 5-benzenetricarboxylate MOFs. Issue 40 (25th September 2019) - Wang, Ce; Yin, Zheng; Ma, Wei-Min; Li, Xi-Yao; Cao, Li-Hui; Cheng, Yu; Yu, Xin-Yu; Ma, Yang-Min
Abstract : A white light MOF was constructed from low-cost 1, 3, 5-benzenetricarboxylate and nontoxic Zinc(ii ) ions, which exhibited near sunlight continuous white-light emission under a wide radiation range of 300 to 390 nm and was used for white-light emitting diodes. Abstract : A new white light MOF was constructed from low-cost 1, 3, 5-benzenetricarboxylate and nontoxic Zinc(ii ) ions. The compound possessed the most sophisticated crystallographic asymmetric unit containing sixteen metal ions and twelve ligands. Near sunlight and human eye friendly white-light emission under a wide ultraviolet radiation range of 300 to 390 nm was observed for this photoemitter, without the use of expensive rare earth and complicated organic ligands.